2013
DOI: 10.1088/2043-6262/4/2/029601
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Characterization of nanostructured PbO2–PANi composite materials synthesized by combining electrochemical and chemical methods

Abstract: The full text of this article is available in the PDF provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…The data given on spectra from figure 4 and table 1 showed that all regarded composites contain PANi owing to vibration signals of benzoid and quinoid ring as well as some main groups similar to those reported in literature [8,12,13]. It explained that PANi in emeraldine salt form co-existed in composite lattice.…”
Section: Infrared Analysissupporting
confidence: 79%
See 4 more Smart Citations
“…The data given on spectra from figure 4 and table 1 showed that all regarded composites contain PANi owing to vibration signals of benzoid and quinoid ring as well as some main groups similar to those reported in literature [8,12,13]. It explained that PANi in emeraldine salt form co-existed in composite lattice.…”
Section: Infrared Analysissupporting
confidence: 79%
“…The obtained oxidation current Δi for methanol in this research was until 85 mA cm −2 (in the case only by cyclic voltammetry), twice to three times as high as that one in our previous report [8] owing to combining chemical and pulsed current methods (only until 30 mA cm −2 ). This explains how PANiPbO 2 composites prepared by combining chemical and cyclic voltammetric methods can more positively catalyse for methanol oxidation than those by chemical and pulsed current methods.…”
supporting
confidence: 46%
See 3 more Smart Citations